The Influence of Emerging Markets on the Pharmaceutical Industry - Maya Tannoury, Bs; Zouhair Attieh, PhD (Elsevier, 2017)
Emerging markets represent an exceptional opportunity for the pharmaceutical industry. Although a precise definition is not yet available, economists define emerging markets as developing prosperous countries in which investment is expected to result in higher income despite high risks. Qualifying a market as emerging is not merely based on the economic status of the country, but also on several criteria that render the definition applicable to each country. Jim O'Neil, retired chairman of asset management at Goldman Sachs, identified leading economies of emerging markets: Brazil, Russia, India, and China (BRIC) and later Brazil, Russia, India, China, and South Africa (BRICS) and then Mexico, Indonesia, South Korea, and Turkey (MIST), which followed years later as the second tier of nations. Sales of the pharmaceutical markets in BRICS and MIST countries doubled in 5 years, reaching a market share of approximately 20%. The shift toward these new markets has been attributed to the large populations, growing prosperity, and increasing life expectancy in BRICS and MIST countries. In addition, companies are experiencing flattened growth of developed markets, expiration of patents leading to the up-selling of less expensive generic drugs, and tight regulations enforced in mature markets. Particular attention must therefore be given to these emerging markets. The strategies adopted by pharmaceutical companies that want to expand in these markets must be tailored to the pace of development of each country. These countries need drugs against infectious diseases and communicable diseases such as sexually transmitted diseases. They are readily exploitable territories for the innovative products of pharmaceuticals. Nevertheless, with the increase in wealth and longevity, a change of lifestyle is occurring. These changes accompany a shift in disease patterns. A disproportionally fast rise in the incidence of noncommunicable diseases such as cardiovascular illnesses, diabetes, and oncologic diseases has been observed in emerging markets, mimicking their Western counterparts. The incidence of diabetes and oncologic diseases is expected to grow by 20% or more by 2030. This shows that pharmaceutical industries will also be able to market their global products in these new countries. Conquering emerging markets can be challenging for industries. These challenges can be grouped into 3 categories: infrastructure development, cost-containment policies, and value-driven drug evaluation. Top strategies considered to overcome these challenges include adequate tailoring and a gain in market.